2022
DOI: 10.1186/s13244-022-01159-x
|View full text |Cite
|
Sign up to set email alerts
|

Phlebosclerotic colitis: an analysis of clinical and CT findings in 29 patients with long-term follow-up

Abstract: Background Phlebosclerotic colitis (PC) is a rare form of nonthrombotic colonic ischemia. This retrospective study analyzed the clinical findings and temporal CT changes in 29 PC patients with long-term follow-up. Methods Twenty-nine patients with characteristic CT features of PC collected between 1997 and 2020 were stratified into the acute abdomen group (AA-group) (n = 10), chronic-progressive group (CP-group) (n = 14) and chronic-stable group (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…More severe mesenteric venous calcification, increased involvement of colonic segments, thicker colonic wall, and the presence of pericolic inflammation seem associated with a higher frequency of clinical symptoms and are indicative of the need for surgery. 1,3,4 In our study, all patients demonstrated varying degrees of venous calcification and colonic wall thickness. Pericolic inflammation was observed in 26 patients (57.78%).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…More severe mesenteric venous calcification, increased involvement of colonic segments, thicker colonic wall, and the presence of pericolic inflammation seem associated with a higher frequency of clinical symptoms and are indicative of the need for surgery. 1,3,4 In our study, all patients demonstrated varying degrees of venous calcification and colonic wall thickness. Pericolic inflammation was observed in 26 patients (57.78%).…”
Section: Discussionmentioning
confidence: 48%
“…This heterogeneity underscores the need for diverse treatment approaches, ranging from supportive care to surgical intervention. [1][2][3][4][5] Mild symptoms can be managed by observation or symptomatic relief medications, whereas severe symptoms necessitate surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Chen et al found that only four of 25 Chinese patients with IMP had history of long-term use of traditional Chinese medicinal materials and medicinal liquor ( 10 ). In a study by Sheung et al involving 29 patients with venous sclerosing colitis, only six used various herbal medicines, and a significant association between herbal medicines and IMP was not established ( 11 ). According to a systematic review of 240 reports by Wang et al, 78.7% of patients had history of herbal medicine intake ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…IMP is pathologically characterized by mucosal ulceration, epithelial ischemic atrophy of the intestinal wall, extensive fibrosis and hyalinization of the submucosa ( 16 ), and marked calcification within the venous wall narrowed by non-inflammatory fibrosis ( 11 ). The clinical signs of IMP are nonspecific and include chronic abdominal pain, diarrhea, and anemia.…”
Section: Discussionmentioning
confidence: 99%